The Effect of Financial Inclusion and Financial Literacy on the Performance of Weaning MSMEs in Bengkalis - Henny Dwi Anggraheni; Ruzikna; Mandataris (PT FORMOSA CENDEKIA GLOBAL, 2024)
The results of this research aim to see the impact of financial inclusion and financial literacy on the performance of weaving MSMEs in Bengkalis sub-district. Bengkalis is a district that is currently developing. The growth of MSMEs also triggers economic growth in the Bengkalis area. One of the MSMEs that is developing is MSMEs in the creative weaving industry sector. There are 273 MSMEs operating in the weaving sector spread across Bengkalis district. The problems faced by weaving MSMEs, even though they have a potential role, are in reality not yet able to develop optimally. a. The results of this research show that it partially has an influence on the performance of weaving MSMEs in Bengkalis sub-district. Likewise, simultaneously it also has an effect. In this research, the performance of weaving MSMEs is able to develop optimally if financial inclusion and financial literacy are properly paid attention to.